2014
DOI: 10.3109/10408444.2014.938802
|View full text |Cite
|
Sign up to set email alerts
|

Granular biodurable nanomaterials: No convincing evidence for systemic toxicity

Abstract: Nanomaterials are usually defined by primary particle diameters ranging from 1 to 100 nm. The scope of this review is an evaluation of experimental animal studies dealing with the systemic levels and putative systemic effects induced by nanoparticles which can be characterized as being granular biodurable particles without known specific toxicity (GBP). Relevant examples of such materials comprise nanosized titanium dioxide (TiO2) and carbon black. The question was raised whether GBP nanomaterials systemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…Gebel et al (2014) proposed that biodurable HARN that do not meet the fiber paradigm may be classified as granular biodurable particles (GBPs). GBPs are classified as low toxicity particles, which may however cause inflammation and acute phase response (Moreno-Horn and Gebel, 2014;Saber et al, 2014), which in turn are risk factors for cardiovascular disease (Saber et al, 2014). Stanton et al (1981) showed that pleural dose to 40 mg of two different types of HNTs in hardened gelatin implanted on to the pleural surface resulted in formation of pleural sarcomas in 9 of 53 rats (17%) 2 years post-exposure as compared to 3 of 488 sham-treated controls (0.6%).…”
Section: Introductionmentioning
confidence: 99%
“…Gebel et al (2014) proposed that biodurable HARN that do not meet the fiber paradigm may be classified as granular biodurable particles (GBPs). GBPs are classified as low toxicity particles, which may however cause inflammation and acute phase response (Moreno-Horn and Gebel, 2014;Saber et al, 2014), which in turn are risk factors for cardiovascular disease (Saber et al, 2014). Stanton et al (1981) showed that pleural dose to 40 mg of two different types of HNTs in hardened gelatin implanted on to the pleural surface resulted in formation of pleural sarcomas in 9 of 53 rats (17%) 2 years post-exposure as compared to 3 of 488 sham-treated controls (0.6%).…”
Section: Introductionmentioning
confidence: 99%
“…1185 The dissolution rate is an essential factor for the grouping and 1186 risk assessment of nanomaterials. Some nanomaterials, such as sil-1187 ver or zinc oxide nanomaterials or cadmium-based quantum dots, 1188 may release toxic ions, particularly in biological samples (Sharma 1189(Sharma et al, 2012Nel et al, 2013;Gebel et al, 2014;Landsiedel et al, 1190 2014a; Pujalté et al, 2014). Alternatively, completely ( (Li et al, 2014;Molina et al, 2014).…”
mentioning
confidence: 96%
“…particles', other nanomaterials may need to be grouped using 995 additional aspects of grouping discussed below depending on the 996 toxicity endpoint. In addition, it is likely false to assume that 997 nano-size alone dictates toxicity (Gebel et al, 2014). (Stefaniak et al, 2005;Gamble, 2011;1179Misra et al, 2012.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Titanium dioxide is mostly explored in the field of photocatalysis, photodegradation, photovoltaics, etc., owing to its efficient optical absorption, low price and chemical stability [9][10][11][12][13][14][15]. Several recent studies have shown that these nanomaterials are biocompatible [16] and environment friendly [17,18]. This material can be amorphous, as well as exhibit polymorphism and exist in three different crystalline forms: anatase, brookite, and rutile [19].…”
Section: Introductionmentioning
confidence: 99%